The “DICVER” Learning Model to Improve Elementary School Students Scientific Thinking Skills - Kadek Dewi Wahyuni Andari; Widodo Ari (Jurnal Ilmiah Sekolah Dasar, 2025)
Scientific thinking skills are essential competencies that need to be developed from the elementary level to enable students to understand scientific concepts deeply and critically. This study aims to examine the extent to which the “DICVER” learning model can enhance elementary school students’ scientific thinking skills. The DICVER model was developed and implemented in science learning, designed based on Kuhn’s indicators of scientific thinking and linked to competencies in scientific literacy. Through the scientific method, the model fosters an understanding of science not only as a means to verify facts and theories but also as a way to build awareness of the Nature of Science. This research employed a quantitative approach using a one-group pretest–posttest design. The sample consisted of 27 elementary school students, with a scientific thinking test used as the research instrument. The collected data were analyzed using a paired sample t-test at a 0.05 significance level. The findings revealed a significant difference in students’ scientific thinking skills before and after the implementation of the DICVER model, with a t-test value of -6.331. These results emphasize that scientific thinking, rooted in the nature of science and its systematic process of evidence-based reasoning, can be effectively improved through structured learning. Thus, the DICVER model contributes significantly to fostering students’ scientific thinking skills in science education.